Treatment of granuloma annulare and related granulomatous diseases with sulphasalazine: a series of 16 cases. (21st July 2020) - Yang, Y.W.; Lehrer, M.D.; Mangold, A.R.; Yiannias, J.A.; Nelson, S.A.; Pittelkow, M.R.
Abstract: Background: Granuloma annulare (GA) and the related annular elastolytic giant cell granuloma (AEGCG) and interstitial granulomatous dermatitis (IGD) are idiopathic histiocytic inflammatory disorders, which are frequently recalcitrant to treatment. Objectives: Evaluate the efficacy of sulphasalazine in treating GA, AEGCG and IGD. Methods: Sixteen patients were identified with granulomatous disease who were treated with sulphasalazine between September 2015 and September 2019. Outcomes were based on patients' and providers' subjective evaluations. Results: Sixteen patients were included in the study (ages 56–89, four male and twelve female). Previous treatments were attempted in fifteen patients. Clinical improvement was seen in fourteen patients (87.5%). Initial improvement was noted within a mean (SD) of 66.4 (35.1) days after starting therapy, with increasing benefits over time. Ten patients (62.5%) reported complete or near‐complete clearance, three patients (18.8%) reported significant improvement, and one (6.3%) reported partial improvement. Twelve patients elected to stop or reduce therapy, resulting in relapse or worsening in five patients. Conclusions: Sulphasalazine may be considered as treatment for GA and GA‐related conditions.